2018
DOI: 10.1177/1550059418792153
|View full text |Cite
|
Sign up to set email alerts
|

Reactivating the Dormant Motor Cortex After Spinal Cord Injury With EEG Neurofeedback: A Case Study With a Chronic, Complete C4 Patient

Abstract: Chronic spinal cord injury (SCI) patients present poor motor cortex activation during movement attempts. The reactivation of this brain region can be beneficial for them, for instance, allowing them to use brain-machine interfaces for motor rehabilitation or restoration. These brain-machine interfacess generally use electroencephalography (EEG) to measure the cortical activation during the attempts of movement, quantifying it as the event-related desynchronization (ERD) of the alpha/mu rhythm. Based on previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…Indeed, it was expected that beta-band ERD would be relatively weaker at the beginning of the priming phase and show gradual strengthening over the course of the study. This would mirror similar work by Lopez-Larraz et al which showed that ERD was significantly enhanced in a chronic C4 AIS A tetraplegic individual following four sessions of upper-alpha band neurofeedback training (25). Instead ERD was strong throughout the study and comparable to the activity of able-bodied individuals (46,53).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Indeed, it was expected that beta-band ERD would be relatively weaker at the beginning of the priming phase and show gradual strengthening over the course of the study. This would mirror similar work by Lopez-Larraz et al which showed that ERD was significantly enhanced in a chronic C4 AIS A tetraplegic individual following four sessions of upper-alpha band neurofeedback training (25). Instead ERD was strong throughout the study and comparable to the activity of able-bodied individuals (46,53).…”
Section: Discussionsupporting
confidence: 86%
“…However, given that the individual in this current study exhibited maximal values of cortical activation at the beginning and throughout the study, it may be that supraspinal excitability was already at its greatest extent, making priming a superfluous addition. Potentially, priming of the nature described herein would benefit only those with impaired cortical activity, such as the variety described by Lopez-Larazz et al, and others (24,25,50).…”
Section: Discussionmentioning
confidence: 90%
“…a bar changing its dimensions according to ongoing rhythmic cortical activity. Previous studies have suggested that neurofeedback training sessions aimed to increase the presence of sensorimotor rhythms in spinal cord injured patients can indeed produce plastic changes resulting in greater desynchronization of sensorimotor rhythms during motor processing (this is possible indirect evidence for increased recruitment of motor cortical rhythms during motor processing states) (López-Larraz et al 2018a). However, while extensive research has been dedicated to validating neurofeedback training BCIs for non-motor conditions, the use of these techniques for motor restoration has received little attention.…”
Section: Bcis Based On Operant Conditioningmentioning
confidence: 99%
“…In patients with lesions to the CNS leading to limb paresis, sensorimotor rhythms tend to be distorted (López‐Larraz et al . 2015, 2018 a ).…”
Section: Introductionmentioning
confidence: 99%
“…EEG neurofeedback is widely used to treat epilepsy [ 62 ]; it is also being administered in novel capacities to treat conditions such as fibromyalgia [ 63 ] or chronic prostatitis [ 64 ] and is commonly adopted in rehabilitation, for example, in patients with amyotrophic lateral sclerosis (ALS) [ 65 ], stroke [ 66 ], spinal cord [ 67 ], and traumatic brain injuries [ 68 , 69 ].…”
Section: Biofeedbackmentioning
confidence: 99%